Daya Inovasi Pada Kinerja Karyawan - Ferri Kuswantoro (Prosiding Seminar Nasional Ekonomi dan Bisnis, 2021)
Innovation is the main support especially in improving employee performance. Many studies had explained the importance of managerial training and team work in pursuing growth. However, studies that explained how the role of innovation in driving the relationship between training and teamwork on employee job satisfaction are rare. The purpose of this research is to examine the role of innovativeness in driving the relationship between training and team work on employee job satisfaction. Using a sample of 165 respondents with questionnaire from employees in general supported by AMOS version 24 the results of the study showed that there was a significant positive effect between teamwork on the innovativeness and employee job satisfaction. There was a significant positive effect between the relationship of innovativeness on employee job satisfaction but there was no significant positive effect between managerial training on the innovativeness and employee job satisfaction. The final result indicated that the innovativeness partially mediated a significant positive relationship between teamwork and employee job satisfaction.